The Muppet Show. Season one [videorecording (DVD)] - Henson, Jim; Oz, Frank (Disney, 2005)
The complete first season of the award-winning television series featuring Jim Henson's Muppets. Includes every episode from the first season, the pilot episode, and a bonus feature disc.